Multi–drug resistant Staphylococcus aureus isolated from milk, chicken meat, beef and egg in Bangladesh - Rahman, Mohammad Anisur; Rahman, AKM Anisur; Islam, Md Ariful; Alam, Md Mahbub (Research in Agriculture Livestock and Fisheries, 2018)
Staphylococcal infection is one of the most common food-borne diseases in the world. Moreover, antimicrobial resistance of pathogenic bacteria, including Staphylococcus (S.) aureus is an emerging problem of food safety. This study was conducted to investigate the prevalence of S. aureus in milk, chicken meat, egg and beef; and to determine the multi-drug resistance (MDR) profile of S. aureus in Mymensingh and Gazipur districts, Bangladesh. A total of 189 samples of milk (n=108), chicken meat (n=51), egg (n=20) and beef (n=10) were collected from Bangladesh Agricultural University dairy farm, American dairy farm, Gazipur and different dairy farms of municipal area and retail shops during July 2016 to June 2018. S. aureus were isolated and identified by conventional methods and polymerase chain reaction (PCR). Antimicrobial susceptibility tests were done through disc diffusion test using 10 commonly used antibiotics. The overall prevalence of S. aureus in all food samples was 43.39%. A total of 39 (76.47%) chicken meat, 25 (23.15%) milk, 11(55%) egg and 07 (70%) beef samples were S. aureus positive through conventional method. Among 82 culture positive samples only 39 samples (47.56%) were confirmed by PCR. Antibiogram study showed that S. aureus isolated from chicken meat were mostly resistant to oxytetracycline (71.79%); and highly sensitive to amikacin (100%) and neomycin (100%). S. aureus isolated from milk samples were highly sensitive to neomycin (100%), and resistant to amikacin (56%). Only 28.57% isolates of S. aureus originated from beef samples were resistant to oxytetracycline and 100 % isolates were sensitive to ciprofloxacin, gentamicin, erythromycin, azithromycin, doxycycline. Similarly, S. aureus isolated from egg samples were resistant to erythromycin (81.82%) and 100% sensitive to amikacin. Out of 41.46% MDR isolates 12%, 53.85%, 90.91% and 0% of the S. aureus originated from milk, chicken meat, egg and beef respectively. The higher prevalence of S. aureus in chicken meat, beef, egg and milk indicates unhygienic production, marketing and processing of these foods. Presence of MDR S. aureus in these foods might pose serious public health threats. Rational use of antibiotics with higher sensitivity should be prescribed in managing poultry diseases to reduce re-emerging MDR in Bangladesh. Res. Agric., Livest. Fish.5(2): 175-183, August 2018